RISK ANALYSIS IN ENTREPRENEURIAL DECISION MAKING - Abdul Rosid (CV. Adiba Aisha Amira, 2025)
Being an entrepreneur means having the courage to take risks. Uncertainty that could result in losses is called risk. Making decisions is a way to weigh and choose between various choices. The approach is a review of the literature with an awareness of prior research findings on risk analysis in entrepreneurial decision making that is obtained from online journal references. This study's findings indicate that decision-making is necessary throughout the entire lifecycle of entrepreneurial endeavors. This includes the planning phase, the implementation phase, or operationalization of activities, and the supervision phase, which entails monitoring, verifying, and evaluating the plan's implementation's outcomes to ensure that the goals are met in terms of quantity, quality, cost, and the effective and efficient use of other resources.